Curative and β cell regenerative effects of α1-antitrypsin treatment in autoimmune diabetic NOD mice - Koulmanda, Maria (National Academy of Sciences, 2008)
Invasive insulitis is a destructive T cell-dependent autoimmune process directed against insulin-producing β cells that is central to the pathogenesis of type 1 diabetes mellitus (T1DM) in humans and the clinically relevant nonobese diabetic (NOD) mouse model. Few therapies have succeeded in restoring long-term, drug-free euglycemia and immune tolerance to β cells in overtly diabetic NOD mice, and none have demonstrably enabled enlargement of the functional β cell mass. Recent studies have emphasized the impact of inflammatory cytokines on the commitment of antigen-activated T cells to various effector or regulatory T cell phenotypes and insulin resistance and defective insulin signaling. Hence, we tested the hypothesis that inflammatory mechanisms trigger insulitis, insulin resistance, faulty insulin signaling, and the loss of immune tolerance to islets. We demonstrate that treatment with α1-antitrypsin (AAT), an agent that dampens inflammation, does not directly inhibit T cell activation, ablates invasive insulitis, and restores euglycemia, immune tolerance to β cells, normal insulin signaling, and insulin responsiveness in NOD mice with recent-onset T1DM through favorable changes in the inflammation milieu. Indeed, the functional mass of β cells expands in AAT-treated diabetic NOD mice.